The Correlation of Physical Activity and Medication Adherence with The Quality of Life in Type 2 Diabetes Mellitus Patients at Randuagung Health Center, Lumajang - Ika Widiya Anggraeni; Mariani; Alwin Widhiyanto (KHD Production, 2024)
Diabetes mellitus is a chronic disease that cannot be cured. Patients with diabetes mellitus will experience various problems in their life processes, which can affect their quality of life. To improve the quality of life of patients, physical activity and medication adherence are necessary. This study aims to determine the correlation between physical activity and medication adherence with the quality of life in diabetes mellitus patients. The research design used a correlational design with a crosssectional approach. The sample consisted of 44 respondents. The study employed the GPAQ, MMAS, and DQOL questionnaires. Data analysis was performed using chi-square. The results showed that most of the physical activity among patients with type 2 diabetes mellitus was categorized as moderate, with 26 (59.1%). Most patients had low medication adherence, with 17 (38.6%) falling into this category, and the majority had poor quality of life, with 20 (45.5%) in this category. The study found a significant correlation between physical activity and quality of life with p = 0.004 (p < α = 0.05) and a significant correlation between medication adherence and quality of life with p = 0.000 (p < α = 0.05). Quality of life is an important factor that can influence an individual's health condition. Physical activity and medication adherence have an impact on the quality of life for patients with type 2 diabetes mellitus. Based on the research findings, develop educational materials that promote the benefits of physical activity and the importance of medication adherence to improve the quality of life for patients.